Bryophytes Harbor Cultivable Actinobacteria With Plant Growth Promoting Potential - Chadabhorn Insuk; Chadabhorn Insuk; Nattakorn Kuncharoen; Naowarat Cheeptham; Somboon Tanasupawat; Wasu Pathom-aree; Wasu Pathom-aree (Frontiers in Microbiology, 2020)
This study was designed to investigate the cultivable actinobacteria associated with bryophytes and their plant growth promoting ability. Thirteen actinobacteria were isolated and tested for their ability to promote growth of plant in vitro and in planta. All isolates were able to produce IAA and siderophores. Six isolates were identified as members of the genus Micromonospora. Five isolates belonged to the genus Streptomyces and one each of Microbispora and Mycobacterium. Micromonospora sp. CMU55-4 was inoculated to rare moss [Physcomitrium sphaericum (C. Ludw.) Fürnr.] and could increase the amount of carotenoid, fresh weight, and dry weight of this moss. In addition, this strain promoted capsule production, and rescued P. sphaericum’s gametophytes during acclimatization to land. Strain CMU55-4 was identified as Micromonospora chalcea based on whole genome sequence analysis. Its plant growth promoting potential was further characterized through genome mining. The draft genome size was 6.6 Mb (73% GC). The genome contained 5,933 coding sequences. Functional annotation predicted encoded genes essential for siderophore production, phosphate solubilization that enable bacteria to survive under nutrient limited environment. Glycine-betaine accumulation and trehalose biosynthesis also aid plants under drought stress. M. chalcea CMU55-4 also exhibited genes for various carbohydrate metabolic pathways indicating those for efficient utilization of carbohydrates inside plant cells. Additionally, predictive genes for heat shock proteins, cold shock proteins, and oxidative stress such as glutathione biosynthesis were identified. In conclusion, our results demonstrate that bryophytes harbor plant growth promoting actinobacteria. A representative isolate, M. chalcea CMU55-4 promotes the growth of P. sphaericum moss and contains protein coding sequences related to plant growth promoting activities in its genome.